PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) TERHADAP HASIL BELAJAR PADA MATA PELAJARAN IPS TERPADU DI SMPN 1 SIAK HULU - Asrina.M, Maretta; Kartikowati, Sri; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the low learning outcomes of students inparticipating in IPS Tepadu learning. The purpose of this study was to determine theeffect of implementing the Two Stay Two Stray (TSTS) cooperative learning model onlearning outcomes in Integrated Social Studies subjects. The population in this studywere all students of class VII SMPN 1 Siak Hulu which consisted of 10 classes. Thesample selection was carried out using a multistage sampling technique so that asample of class VII H and VII J was produced, each with 32 students. The datacollection techniques were observation using the research instrument, the teacher andstudent activity observation sheet, and the test technique using the pre-test and post-testresearch instruments. Furthermore, the data were analyzed using the normality test, ttest, and normalized gain test with the help of SPSS Version 2. When viewed from theresults of the statistical test analysis with the t test data of the post-test values of theexperimental and control classes, it is obtained that the sig value is 0.000 <0.05 and itcan be said that there is a significant difference between the experimental class and thecontrol class. And when viewed from the normalized gain test, the experimental classobtained an n-gain value of 0.59 in the moderate category, it can be concluded that theTSTS learning model in the experimental class has a positive effect on learningoutcomes in integrated social studies subjects.Key Words: Cooperative Learning Model Two Stay Two Stray, Student Learning Out Comes